Social meaning of Vilnius vowel lengthening. The research of pupils’ subconscious attitudes - Čičirkaitė, Ramunė (Taikomoji kalbotyra, 2014)
It is not enough just to describe the distribution of linguistic variants in a speech community in order to explain language variation and change in apparent time, it is important to examine what attitudes language users have towards them as well as social meanings ​​attributed to them. To date the social meaning of vowel lengthening as a relevant feature of Vilnius speech has, however, not been studied. In February–March in 2014 speaker evaluation experiment was conducted in two socially and ethnically unmarked schools with Lithuanian as the language of instruction. The schools were ranked in the middle position in the rating of city schools; all of them were located in two socially unmarked boroughs of Vilnius. The experiment aimed at determining the social meanings that vowel lengthening acquires among Vilnius city pupils. A total of 231 senior (9–10) class pupils took part in the study. The experiment has confirmed the hypothesis that vowel lengthening in Vilnius speech is not evaluated ambiguously and has more than one social meaning. It is the articulatory context, in the other words – the cluster of other pronunciation features of a speaker (or stimuli type) that is decisive in which of the meanings is actualized. It has also showed a clear hierarchization of the stimuli types which reveal natural variability of short vowel lengthening in the speech community of Vilnius: 1) Kam+GalLT, 2) Neu, 3) Kam and 4) Kam+GalSL. The study has revealed that if vowel lengthening in the stem of the word and in the inflectional ending occurs in the articulatory context of the speakers of Lithuanian origin, it is perceived as a marker of high social status, power, high professional competence of the speaker as well as representing businessman profession, a speaker who could work as a newsreader, hold leadership positions. Personal traits like „educated“, „wealthy“, „successful“, „managing“, „youthful“, „urban“ and „having a good job“ have mostly been assigned to the latter types of speakers with statistically significant difference. If vowel lengthening occurs in the articulatory context of the speakers of Slavic origin, it is recognized as Slavic and associated with low social status, linked to services and working-class occupations. In addition, all the mentioned personal traits to this type of stimuli have been assigned most rarely by the pupils. Only the stem lengthening articulatory context has been linked to the category of provinciality and this stimuli type representing speakers have been mostly considered to be suitable for service occupations.
Keywords: lengthening of stressed short vowels; Vilnius speech; social meaning; subconscious atittudes; speaker evaluation experiment; sociolinguistics